2004
DOI: 10.4141/p02-174
|View full text |Cite
|
Sign up to set email alerts
|

Root maggots (Delia spp., Diptera: Anthomyiidae) in prairie canola (Brassica napus L. and B. rapa L.): Spatial and temporal surveys of root damage and prediction of damage levels

Abstract: Soroka, J. J., Dosdall, L. M., Olfert, O. O. and Seidle, E. 2004. Root maggots (Delia spp., Diptera: Anthomyiidae) in prairie canola (Brassica napus L. and B. rapa L.): Spatial and temporal surveys of root damage and prediction of damage levels. Can. J. Plant Sci. 84: 1171-1182. The levels of infestation and damage to canola taproots caused by crucifer-feeding root maggots (Delia spp.)(Diptera: Anthomyiidae) were determined through surveys of commercial crops across the canola growing regions of western Canada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…3.3); remaining frass and microbes alone therefore can not be responsible for the elevated sulfide emissions. This also precludes that root pathogens entering the roots at the damage sites have a major effect [128], as they would also remain after larval feeding has stopped. C6 wound compounds were not detected in our analyses, neither after insect damage nor after mechanical wounding.…”
Section: Discussionmentioning
confidence: 99%
“…3.3); remaining frass and microbes alone therefore can not be responsible for the elevated sulfide emissions. This also precludes that root pathogens entering the roots at the damage sites have a major effect [128], as they would also remain after larval feeding has stopped. C6 wound compounds were not detected in our analyses, neither after insect damage nor after mechanical wounding.…”
Section: Discussionmentioning
confidence: 99%
“…Location also strongly affected maggot damage, with much more damage occurring on roots at Melfort than at Saskatoon (Table 1). Previous work has found greater maggot feeding in northern areas of Saskatchewan than in central or southern locations (Soroka et al 2004). …”
Section: Soroka and Elliott -Seed Size Does Not Affect Maggot Damage 909mentioning
confidence: 90%
“…Weather, principally previous year temperatures (Soroka et al 2004) and current year precipitation (Turnock et al 1992), have been shown to greatly influence Delia biology. Location also strongly affected maggot damage, with much more damage occurring on roots at Melfort than at Saskatoon (Table 1).…”
Section: Soroka and Elliott -Seed Size Does Not Affect Maggot Damage 909mentioning
confidence: 99%
See 1 more Smart Citation
“…The root-feeding species of Delia RobineauDesvoidy (Diptera: Anthomyiidae) have become more widespread and injurious to canola (oilseed cultivars of Brassica napus L. and B. rapa L. (Brassicacae)) on the Canadian prairies as the area planted has increased (Soroka et al 2004). In regions of the prairies with more than 250 mm of rainfall from June to August, the cabbage maggot, D. radicum (L.), is the most abundant Delia species attacking canola (Griffiths 1986b).…”
Section: Introductionmentioning
confidence: 99%